Comparing the broth enrichment-multiplex lateral flow immunochromatographic assay with real time quantitative PCR for the rapid detection of carbapenemase-producing organisms in rectal swabs - Wang, Yue; Song, Huijuan; Xu, Min; Li, Dengju; Ran, Xiao; Sun, Ziyong; Chen, Zhongju (BMC infectious diseases, 2023)
Background Rapid and accurate identification of carbapenemase-producing organism (CPO) intestinal carriers is essential for infection prevention and control. Molecular diagnostic methods can produce results in as little as 1 h, but require special instrumentation and are expensive. Therefore, it is urgent to find an alternative method. The broth enrichment-multiplex lateral flow immunochromatographic assay was recently reported, but using it to directly detect CPO intestinal carriers in rectal swabs still requires the evaluation of many samples. The aim of this study was to compare the performance of these two methods, and to explore the control measures of CPO infection. Methods Through CPO selective culture, PCR and DNA sequencing, 100 rectal swabs confirmed to be CPO-positive and 100 rectal swabs with negative results were collected continuously. After eluting the rectal swabs with saline, three aliquots were used: one for counting, one for detection by Xpert Carba-R, and one for culture in broth for 0 h, 1 h, 2 h, 3 h and 4 h, followed by NG-Test CARBA 5 assessment. The sensitivity and specificity of the NG-Test CARBA 5 method after different incubation times were calculated. The limit of detection (LoD) of this assay after 4 h broth incubation was estimated by examining the bacterial suspensions and simulated faecal suspensions prepared with CPOs producing different types of carbapenemases. Results Xpert Carba-R demonstrated a combined sensitivity of 99.0% and specificity of 98.0%. The sensitivity and specificity were higher than 90.0% for the different enzyme types. The specificities of five common carbapenemases detected by the broth enrichment NG-Test CARBA 5 combined method after different incubation times were 100%. The sensitivities increased with increasing incubation time. At 4 h, the Klebsiella pneumoniae carbapenemase (KPC), New Delhi metallo-beta-lactamase (NDM), imipenemase (IMP), Verona integron-encoded metallo-beta-lactamase (VIM), and oxacillinase (OXA) -48 detection sensitivities were 93.0%, 96.3%, 100%, 100% and 85.7%, respectively. The LoDs were between 10 2 and 10 4 CFU/mL for all five enzymes after 4 h of incubation. Conclusions This investigation highlighted that the broth enrichment-multiplex lateral flow immunochromatographic assay can be used as a new method for screening CPOs in rectal swabs.